The Effect of Changes in Physical Activity Behaviour on Depressive Symptoms Among European Older Adults - De Moraes-Ferrari, G (University School of Physical Education in Wroclaw, 2023)
Purpose. Physical activity is associated with lower odds of depression symptoms among older adults. However, little is known about the effect of changing physical activity behaviour on depressive symptoms. The present study aimed to analyse the effects of changing physical activity trajectory on depressive symptoms in older people. Methods. Data from the Survey of Health, Ageing and Retirement in Europe wave 5 and wave 6 were analysed. The EURO-D 12-item scale measured depressive symptoms, and physical activity (of moderate and vigorous intensity) was self-reported. Multivariate binary logistic regressions were conducted to assess the association between physical activity and depression symptoms. Results. The study involved 6431 participants (mean age: 72.7 years). Moderate and vigorous physical activity was significantly associated with lower odds of depression symptoms in men and women. Moderate physical activity, performed once a week (men: OR = 0.31, 95% CI: 0.21-0.45; women: OR = 0.67, 95% CI: 0.54-0.84) and more than once a week (men: OR = 0.41, 95% CI: 0.32-0.52; women: OR = 0.56, 95% CI: 0.47-0.66), decreased the odds of having depression compared with remaining less active. Similar results were seen for vigorous physical activity in both men and women. Conclusions. Moderate-to-vigorous physical activity, undertaken at least once a week, is a safe and feasible behaviour to deal with depressive symptoms among older adults. © Wroclaw University of Health and Sport Sciences.